Cesarean in Adolescents at the Rural Hospital of Neisu (Democratic Republic of Congo): Epidemiological Aspects and Neonatal and Maternal Prognosis - Nadi Aninyesi Jeanine; J. D. Bosenge Nguma; S. Nobikana; Likilo Osundja; S. K. V. Juakali; Komanda Likwekwe; Katenga Bosunga (Archives of Current Research International, 2019)
Aim: We attempted to determine the epidemiological aspect of cesarean section performed in adolescent girls at Neisu Rural Hospital, DR Congo, and maternal and neonatal prognosis, whereby to contribute to the reduction of maternal and neonatal morbidity and mortality. Methods: Descriptive cross-sectional study from January 1st, 2016 to June 30th 2018, involving 114 cases of caesarean section of 13 to 19 year-olds. Maternal and perinatal data were analyzed on the SPSS 20.0 software. Results: The prevalence of caesarean section among adolescents was 24.8%. The majority of female deliveries had a low level of education (80.7%), half were married, 30.7% were transfer cases, 77.2% were primiparous, and 100% christian and 81.6% had not followed quality prenatal consultations. Cesarean section was done in emergency (97.4%) under spinal anesthesia (69.3%) and especially indicated for feto-pelvic disproportion (69.3%). In newborns there was: 1.8% of prematurity; 21.1% of low weight; 14.9% of resuscitation; 3.5% of Apgar <7 in the 5th minute; 9.6% of neonatal infection and 43.9‰ perinatal mortality. Concerning the maternal prognosis: 10.5% of severe anemia; 16.7% of parietal infection; 16.7% endometritis and 8.8‰ of maternal mortality. Conclusion: The cesarean section in adolescent girls to Neisu is a public health problem and the fetal-maternal prognosis is worrying.